Insights into the functions and RNA binding of Trypanosoma brucei ZC3H22, RBP9 and DRBD7 - Erben, Esteban D.; Leiss, Kevin; Liu, Bin; Inchaustegui Gil, Diana Patricia; Helbig, Claudia; Clayton, Christine (Parasitology, 2021)
Trypanosoma brucei is unusually reliant on mRNA-binding proteins to control mRNA fate, because its protein-coding genes lack individual promoters. We here focus on three trypanosome RNA-binding proteins. ZC3H22 is specific to Tsetse fly forms, RBP9 is preferentially expressed in bloodstream forms; and DRBD7 is constitutively expressed. Depletion of RBP9 or DRBD7 did not affect bloodstream-form trypanosome growth. ZC3H22 depletion from procyclic forms caused cell clumping, decreased expression of genes required for cell growth and proliferation, and increased expression of some epimastigote markers. Apart from decreases in mRNAs encoding enzymes of glucose metabolism, levels of most ZC3H22-bound transcripts were unaffected by ZC3H22 depletion. We compared ZC3H22, RBP9 and DRBD7 RNA binding with that of 16 other RNA-binding proteins. ZC3H22, PUF3 and ERBP1 show a preference for ribosomal protein mRNAs. RBP9 preferentially binds mRNAs that are more abundant in bloodstream forms than in procyclic forms. RBP9, ZC3H5, ZC3H30 and DRBD7 prefer mRNAs with long coding regions; UBP1-associated mRNAs have long 3′-untranslated regions; and RRM1 prefers mRNAs with long 3′or 5′-untranslated regions. We suggest that proteins that prefer long mRNAs may have relatively short or degenerate binding sites, and that preferences for A or U increase binding in untranslated regions.